Herodotus, Histories, Book V : Text, Commentary, and Vocabulary - Peek, Philip S. (Oklahoma Series in Classical Culture Ser, 2018)
Book V of the Histories focuses on the Persians and their expansion into Thrakia and Makedonia, as well as their conflict with the Greeks of Ionia. Beginning in the timeless legends of prehistory, Herodotus discusses the customs of the Thrakians, offers insight into Sparta's mindset, and narrates the struggle to restore democracy at Athens after the reign of the tyrant Peisistratos